Students’ Learning Engagement in Writing Class: A Task-Based Learning - Nurmalinda Maharani Farizka; Asih Santihastuti; Bambang Suharjito (Yayasan Visi Intan Permata, 2020)
Students’ degree of interest, attention, and curiosity are some indications of students’ learning engagement which are very important to be noted down by every teacher. Knowing what makes students focused on what they are learning or doing in the class will be a great assistance for teacher in creating meaningful activities which at the end promotes their engagement and motivation. This study was intended to find out students’ learning engagement during a writing class which was designed as a task based learning. The students were assigned to some collaborative activities in composing writings. The researcher observed students’ activities especially during the pre and while writing and found out that one reason among others that made students unable to actively engaged at the beginning of the activity was failing to understand the teacher’s instructions. This problem, however, was solved once they understood the tasks clearly and able to enjoy what they were doing in class. In other words, students’ engagement could happen if the activities are meaningful for them.